1997
DOI: 10.1021/ac9611733
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Analytical Applicability of Luminol-Specific Extrinsic Lyoluminescence of UV-Irradiated Potassium Peroxodisulfate

Abstract: Luminol shows strong chemiluminescence with an emission maximum at ∼430 nm in the presence of sulfate radicals. Sulfate radicals were produced by the dissolution of UV-irradiated potassium peroxodisulfate powder in aqueous luminol solutions. The UV irradiation at 6.7 eV produces a solid solution of sulfate radical in potassium peroxodisulfate by rupturing −O−O− bonds, as in solution, but now the solid solution is stable in a time scale of years in dryness. In the present system, luminol chemiluminescence is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Quartz-distilled water was used in all solutions. The safety precautions required in handling of the reagents have been presented previously. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quartz-distilled water was used in all solutions. The safety precautions required in handling of the reagents have been presented previously. , …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we have recently demonstrated that luminol also shows strong ECL during cathodic pulse polarization of oxide-covered aluminum electrodes in aqueous solution when highly oxidizing radicals are cathodically generated . However, luminol shows strong CL in the presence of sulfate radicals generated by other methods, as well, and does not require necessarily the reduction of luminol or its follow-up products . When sulfate radicals are generated in aqueous Ru(bpy) 3 2+ solution in the absence of strong reductants no CL is generated…”
mentioning
confidence: 99%
“…Secondly, a gaseous product N2 was produced during the model CL reaction. 20,23 This resulted in unstable electric currents, and thus unstable electroosmotic flow during the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…V vs. SHE) [53] by hydrogen abstraction as the main secondary radicals (84.3%) [40,54]. Obviously, the reducing secondary radicals cannot excite ECL in the present system.…”
Section: Effect Of Free Radical Scavengers On the Eclmentioning
confidence: 99%